2021
DOI: 10.1094/pdis-10-20-2102-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Fusarium equiseti Causing Seedling Death on Sugar Beet in Minnesota, U.S.A.

Abstract: In May 2019, sugar beet (Beta vulgaris L.) seedlings with symptoms of wilting and root tip discoloration and necrosis were found in Moorhead (46.5507° N, 96.4208° W), Minnesota, USA. Roots of infected seedlings were surface sterilized with 10% bleach for 15 seconds, rinsed with sterile distilled water and cultured on water agar (MA Mooragar®, Inc, CA) for 3 days at 23 ± 2°C. Isolates were transferred to carnation leaf agar (CLA) and incubated at room temperature (22°C) under fluorescent light for 14 days. Abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Isolation, DNA Extraction, and Draft Genome Sequencing Procedures for isolation, DNA extraction, library preparation, and draft genome sequencing are available in Navasca et al, 2023. In brief, we isolated Fusarium solani from galled sugarbeet by excising and sterilizing small tissues with 0.5% v/v sodium hypochlorite for 10 minutes and washing with sterile distilled water. We extracted high-molecular-weight DNA from the mycelia of pure culture F. solani sugarbeet isolate strain SB1 grown in PDB for five days following the instructions of Liu et al (2021). Agilent TapeStation and Qubit 4.0 determined the DNA quality and quantity, respectively.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation, DNA Extraction, and Draft Genome Sequencing Procedures for isolation, DNA extraction, library preparation, and draft genome sequencing are available in Navasca et al, 2023. In brief, we isolated Fusarium solani from galled sugarbeet by excising and sterilizing small tissues with 0.5% v/v sodium hypochlorite for 10 minutes and washing with sterile distilled water. We extracted high-molecular-weight DNA from the mycelia of pure culture F. solani sugarbeet isolate strain SB1 grown in PDB for five days following the instructions of Liu et al (2021). Agilent TapeStation and Qubit 4.0 determined the DNA quality and quantity, respectively.…”
Section: 1mentioning
confidence: 99%
“…Recently, we reported F. solani as an opportunistic pathogen of sugarbeet (Navasca et al, 2023). This isolate, F. solani strain SB1, was recovered from dark galls of sugarbeets, with symptoms that differ from other Fusarium diseases in sugarbeets (Hanson, 2006; Rivera et al, 2008; Secor et al, 2014; Khan et al, 2021). Electron microscopy and sequencing work confirmed that the galls contain sugarbeet material.…”
Section: Introductionmentioning
confidence: 99%
“…We identified distinct fungal signatures within the oral cavity of nestling black kites that were associated with oral disease or different environmental pressures. In particular, the oral disease-associated fungal signature (subcluster B) encompassed opportunistic pathogens of plants and, more rarely, of vertebrates (including humans), such as F. incarnatum-equiseti species complex (Khan et al, 2021), Penicillium brevicompactum (Caro-Vadillo et al, 2007), Alternaria sp. (Williams et al, 2008), Mucor irregularis (Tang et al, 2021), M. hiemalis (Desai et al, 2013) and R. oryzae (Doub et al, 2020).…”
Section: Anthropogenic and Natural Environmental Factors Have A Great...mentioning
confidence: 99%
“…It was recently isolated from the seeds of the fragrant wallflower (Matthiola longipetala) showing rot (Ivanović et al, 2020). Khan et al (2021) noted that F. equiseti was responsible for seedling death in sugar beet.…”
Section: Introductionmentioning
confidence: 99%